Modernist aesthetics and existentialist thought in J.M. Coetzee`s "The Childhood of Jesus" - Glebova, Olga (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
J.M. Coetzee`s art is deeply rooted in European literary tradition and reflects the complicated relationships between two twentieth-century European avant-garde movements - modernism and postmodernism.
Keywords: modernism; existentialism; philosophical novel; allegory; Coetzee, John Maxwell (1940- )